Antagonistic Effect of Two Indigenous Phosphate Solubilizing Bacteria, Burkholderia contaminans PSB3 and Acinetobacter baumannii PSB11 Isolated From Different Crop Soils - RULLY ADI NUGROHO; VINCENTIA IRENE MEITINIARTI; CHRISSEPTINA DAMAYANTI (Indonesian Society for microbiology, 2020)
Phosphorus is the most important key element in the nutrition of plants. Although P is abundant in soils, it is a major limiting factor for plant growth as it is in an unavailable form for roots uptake. Phosphate solubilizing bacteria (PSB) has ability to convert insoluble form of P to an available form. This study was aimed at screening and characterizing phosphate-solubilizing bacteria from manure and different rhizosphere and to ascertain a potential benefit to use mixed cultures to improve P solubilization. A total of 12 PSB colonies were isolated on Pikovskaya’s agar medium containing tricalcium phosphate. Out of 12 bacterial isolates, 2 isolates showed high phosphate solubilization index (2.17 and 1.83, respectively) were selected for further study. Based on the 16S rRNA gene sequence analysis, PSB3 was closely related to Burkholderia contaminans (99%), and PSB11 was closely related to Acinetobacter baumannii (99%). The mean P dissolved in liquid cultures of PSB3 and PSB11 in a 14-day incubation were 96.7 and 39.3 mg l-1, respectively. Mixed inoculation of B. contaminans PSB3 and A. baumannii PSB11 could not increase the solubilization activity significantly, suggesting there is antagonistic behavior of one isolate towards another. As the interaction of these two isolates may be antagonistic, co-inoculation of these bacteria for P solubilization is not recommended. However, further study is needed to confirm these results.